Birth and Adoptive Parent Antisocial Behavior and Parenting: A Study of Evocative Gene–Environment Correlation. Issue 2 (26th September 2016) - Klahr, Ashlea M.; Burt, S. Alexandra; Leve, Leslie D.; Shaw, Daniel S.; Ganiban, Jody M.; Reiss, David; Neiderhiser, Jenae M.
Abstract : Negative parenting is shaped by the genetically influenced characteristics of children (via evocative r GE) and by parental antisocial behavior; however, it is unclear how these factors jointly impact parenting. This study examined the effects of birth parent and adoptive parent antisocial behavior on negative parenting. Participants included 546 families within a prospective adoption study. Adoptive parent antisocial behavior emerged as a small but significant predictor of negative parenting at 18 months and of change in parenting from 18 to 27 months. Birth parent antisocial behavior predicted change in adoptive father's (but not mother's) parenting over time. These findings highlight the role of parent characteristics and suggest that evocative r GE effects on parenting may be small in magnitude in early childhood.